Emulsions : structure, stability and interactions - Petsev, D. N. (Dimiter Nikolov), 1962- (Interface science and technology, 2004)
Emulsion science is rapidly developing due to its practical importance and the fundamental challenges that it offers. Due to its complexity, there is still a significant lack of understanding about emulsions. With its comprehensive and rigorous approach, Emulsions: Structure, Stability and Interactions is the perfect 'stand-alone' source of information for scientists looking to obtain up-to-date knowledge about the fundamentals of emulsion science and those looking to familiarize themselves with the subject in greater detail. While each chapter presents a concise review on a specific topic, the book offers a consistent presentation of the important physical concepts relevant to emulsions. * Full and comprehensive presentations * Rigorous approach to each topic, providing in-depth information * Acts as a stand-alone' source of information.